The relationship between maternal self-differentiation and behavioral disorders in children with autism: The mediating role of maternal mental health - Gholamali Jafari, Seyyed; Heidari, Alireza; Asgari, Parviz; Esmaeili, Somayeh (Journal of Shahrekord University of Medical Sciences, 2025)
Background and aims: Autism spectrum disorder (ASD) is a multifaceted condition that significantly impacts social interactions, communication, and behavior. Given the profound effects of ASD on families, it is essential to understand the factors influencing the well-being of caregivers, particularly mothers. This study aimed to investigate the relationship between maternal self-differentiation and behavioral disorders in children with ASD, emphasizing the mediating role of maternal mental health. Methods: This study utilized a descriptive-correlational design employing structural equation modeling (SEM). The population comprised all children diagnosed with ASD and their mothers registered with the Autism Association in Ahvaz in 2023. A convenience sample of 262 participants was selected from the Autism Association of Ahvaz. The data were collected using the Child Behavior Checklist (CBCL), the Differentiation of Self Inventory, and the Symptom Checklist-90-Revised (SCL-90-R). Following data collection, Pearson correlation analysis and SEM were performed using SPSS-27 and AMOS-24. Results: The findings indicated a significant negative correlation between maternal self-differentiation and child behavioral disorders (β=-0.13, P=0.029). Additionally, a significant positive correlation was identified between maternal self-differentiation and maternal mental health (β=0.37, P=0.001). However, there was a significant negative correlation between maternal mental health and child behavioral disorders (β=-0.58, P=0.001). An indirect relationship was also found between maternal self-differentiation and child behavioral disorders, mediated by maternal mental health (β=-0.32, P=0.010). All goodness-of-fit indices for the model fell within acceptable ranges. Conclusion: Overall, it was revealed that the emotional well-being of mothers and their capacity to maintain a distinct sense of identity are significantly associated with their children’s behavior, particularly in the context of ASD. Enhancing maternal mental health and fostering self-differentiation may yield positive outcomes for children with ASD.